2015
DOI: 10.1080/15384047.2015.1095397
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 receptor-targeted liposomal doxorubicin as a model for enhancing cellular uptake and antitumor efficacy in murine colorectal cancer

Abstract: Our previous studies showed that colorectal tumor has high interleukin-4 receptor α (IL-4Rα) expression, whereas adjacent normal tissue has low or no IL-4Rα expression. We also observed that human atherosclerotic plaque-specific peptide-1 (AP1) can specifically target to IL-4Rα. In this study, we investigated the therapeutic efficacy and systemic toxicity of AP1-conjuagted liposomal doxorubicin. AP1 bound more strongly to and was more efficiently internalized into IL-4Rα-overexpressing CT26 cells than CT26 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…and Chi et al. conjugated AP1 to liposomes for delivering doxorubicin to murine colorectal cancer IL‐4 receptor positive cells (CT26‐IL4R) and human squamous non‐small cell lung cancer (H226), respectively 79b,82. In these in vivo studies, tumor uptake of liposomes was enhanced with the use of the peptide specific ligand to IL‐4R (Figure C) and tumor volume was significantly decreased in IL‐4R peptide conjugated liposomes as compared to unconjugated liposomes 79b,82…”
Section: Common Tumor Targets For Receptor‐mediated Drug Deliverymentioning
confidence: 98%
See 2 more Smart Citations
“…and Chi et al. conjugated AP1 to liposomes for delivering doxorubicin to murine colorectal cancer IL‐4 receptor positive cells (CT26‐IL4R) and human squamous non‐small cell lung cancer (H226), respectively 79b,82. In these in vivo studies, tumor uptake of liposomes was enhanced with the use of the peptide specific ligand to IL‐4R (Figure C) and tumor volume was significantly decreased in IL‐4R peptide conjugated liposomes as compared to unconjugated liposomes 79b,82…”
Section: Common Tumor Targets For Receptor‐mediated Drug Deliverymentioning
confidence: 98%
“…The IL‐4 receptor is known to be overexpressed in glioblastomas, pancreatic, ovarian, lung, renal, breast, and colorectal cancers . IL‐4 causes the direct inhibition of cancer in vitro .…”
Section: Common Tumor Targets For Receptor‐mediated Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…The antitumor effect of doxorubicin has been widely reported (61). In a previous study, the liposomal form of doxorubicin was conjugated with a ligand of the atherosclerotic plaque-specific peptide-1 (AP1), a peptide characterized by its ability to bind IL-4R; Yang et al (62) proposed that AP1-conjugated liposomal doxorubicin exhibits an increased and selective cytotoxic effect on CRC cells, and has potential as a targeted anticancer therapy. Collectively, the aforementioned studies demonstrated that the inhibition of IL-4, IL-4R, IL-13Rα1 and IL-13Rα2 may be beneficial for colon cancer.…”
Section: Targeting Il-4 Il-13 Il-4r and Il-13rα2 In Colon Cancer Thmentioning
confidence: 99%
“…This configuration of monolayer lipids is outside of the scope of this paper and reviews on this subject can be found elsewhere [30]. It should be noted, however, that many similar applications involving liposomes, such as tumor drug delivery and gene therapy, and targeted imaging are being pursued in this field [31,32,33,34,35,36].…”
Section: Ultrasoundmentioning
confidence: 99%